The stability of tide gauges in the South Pacific determined from multi-epoch geodetic levelling, 1992 to 2010 - El-Mowafy, Ahmed; Deo, M.; Govind, R. (Taylor and Francis, 2013)
Tide gauge data is important for determining global or local sea level rise with respect to a global geocentric reference frame. Data from repeated precise levelling connections between the tide gauges and a series of coastal and inland benchmarks, including Continuous GPS (CGPS) benchmarks, are used to determine the stability of tide gauges at 12 locations in the South Pacific. The method for determining this stability is based on a constant velocity model which minimises the net movement amongst a set of datum benchmarks surveyed since the installation of the tide gauges. When assessed at a 95% confidence interval, and with the exception of the Solomon Islands, none of the tide gauges were found to be in motion relative to their CGPS benchmarks. The Solomon Islands estimate is considered to be unreliable since the CGPS benchmark was recently established and has been surveyed fewer than three times. In Tonga and Cook Islands, the tide gauges were found to be disturbed or affected by survey errors whereas the Vanuatu results were affected by earthquakes.